The Effect of Bio-Optimised Light in The School Environment on The Cognitive Functions of Pupils - Nosko, Martin (Advances in Social Sciences Research Journal, 2024)
The article discusses the impact of bio-optimised lighting in school environments on the cognitive functions and abilities of pupils. The article presents the results of foreign research in the field, as well as the initial findings of the authors’ research conducted in a school. The research findings confirm a statistically significant relationship in the context of light and cognitive functions such as attention, thinking, problem-solving, and personal pace. The results suggest that in today’s schools, more attention needs to be paid to the quality of lighting in classrooms. This is crucial if we want future generations to have the opportunity to spend time in a wholesome school environment and to be provided with a comprehensive, supportive, and developmental educational process.